Who Has the Right to the Post-Socialist City? Writing Poland as the Other of Marxist Geographical Materialism - Kamil Rusiłowicz (European Journal of American Studies)
The article opens with a thesis that the post-socialist city is not part of the neoliberal world theorized by David Harvey. By way of comparison, the text discusses Paul Giles’s The Global Remapping of American Literature which is a successful endeavor because the history of American novel is abundant in examples that fit Harvey’s model. The fact that small American factory towns that were unable to successfully accomplish deindustrialization are not accounted for in Giles’s scholarship does not diminish the strength of the scholar’s argument. However, these towns – the blind spot of Harvey’s and Giles’s criticism – bear striking resemblance to the post-socialist city present in the post-1989 Polish literature. Therefore, the analysis of the post-socialist city may provide insightful comments on both Polish and American literary representations of small factory towns.Focusing on Mariusz Sieniewicz’s Czwarte niebo, the article analyzes how the post-socialist city remains a repository of the state-controlled past and resists adaptation to the globalized world of flexible accumulation. It attempts to answer the following questions: What is the position of the post-socialist city within the free-market neoliberal economy? How does the residue of the past built into the fabric of the functionalist space affect its inhabitants? What prevents the residents of the post-socialist city from entering what Harvey calls the space of flexible accumulation? And finally, how can the inhabitants of the post-socialist city reclaim public space?